2016
DOI: 10.12669/pjms.326.11274
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura - analysis of clinical features, laboratory characteristics and therapeutic outcomeof 24 patients treated at a Tertiary Care Center in Saudi Arabia

Abstract: Objective:Thrombotic thrombocytopenic purpura (TTP) is a life-threatening disease. The primary aim was overall response rate (ORR) assessment in the treated patientsMethods:This retrospective study included 24 patients treated during 2006-2015. TTP patients with microangiopathic hemolysis (MAHA) and thrombocytopenia were included. We analyzed clinical features, laboratory characteristics and treatment outcomes of 24 TTP patients treated at our tertiary care center (KFMC).Results:Twenty-four TTP patients (18 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 21 publications
2
25
3
Order By: Relevance
“…In contrast, to reports of TTP in other parts of the world, in this study, TTP was most commonly secondary to, or associated with, HIV infection ( n = 32/41,78.0%). This finding confirms the association of HIV in other previous South African studies .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, to reports of TTP in other parts of the world, in this study, TTP was most commonly secondary to, or associated with, HIV infection ( n = 32/41,78.0%). This finding confirms the association of HIV in other previous South African studies .…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, a median (range) duration of 10.0 daily (7.0‐15.0 daily) TPEs were administered at initial disease presentation. The number of TPEs reportedly required in other centres is variable . A similar median (range) number of TPEs of 12.0 (7.0‐17.0) was reported in a SA cohort of 20 patients with HIV‐associated TTP …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…As an initial therapy, all patients in our series received TPE with a median of seven sessions; this is less than the medians of 8 to 21 sessions reported elsewhere, with the exception of a Chinese report in which the median was 3 . The response rate achieved in our patients was slightly lower (80%) compared to studies where more TPE sessions were performed (82%‐90%), but higher than that reported in the Chinese population where fewer TPE sessions were performed (70%) .…”
Section: Discussioncontrasting
confidence: 62%